Dinamika Pemasaran Digital: Pengaruh Influencer Tiktok dan Ulasan Produk terhadap Keputusan Pembelian Produk Fashion Muslim pada Generasi Z di Stabat Lama Langkat - Elvina Elvina; Tri Dessy Fadillah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of TikTok influencers and product reviews on Generation Z’s purchasing decisions regarding Muslim fashion products in Stabat Lama, Langkat Regency. The growth of digital commerce has transformed consumption patterns among semi-urban communities, particularly among young people who are active on social media. This study employs an associative quantitative approach using purposive sampling on 100 Generation Z respondents who actively use TikTok and have previously purchased Muslim fashion products online. Data were collected via a Likert-scale questionnaire and analyzed using multiple linear regression. Based on the presented research data, the following are the key percentage points: Model Contribution (R-Square): The variables TikTok Influencers and Product Reviews together influence purchasing decisions by 61.8%. Other Factors: The remaining 38.2% is influenced by variables outside the scope of this study, such as product price or quality. Partial Effects: Product reviews have a more dominant influence (beta = 0.581) compared to TikTok influencers (beta = 0.417). The results indicate that TikTok influencers have a positive and significant effect on purchase decisions. Product reviews also have a positive and significant influence, with a more dominant contribution compared to influencers. Simultaneously, both variables make a significant contribution to purchasing decisions. These findings confirm that the integration of influencers’ visual appeal and the credibility of customer reviews is an effective strategy in Muslim fashion marketing in semi-urban areas.